Strategi Realokasi Anggaran sebagai Referensi Struktur Anggaran Daerah yang Efisien - Arifudin Miftakhul Huda; Nur Imroatun Sholihat (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2023)
The Covid-19 pandemic has prompted the nation to make several adjustments, including adjustments to regional budgeting strategies to accommodate the budget for handling the impact of the pandemic. In 2020, the regional government (RG) reallocated the budget without support of adequate considerations related to spending priorities. This paper aims to determine the priority score per regional expenditure item using the Analytical Hierarchy Process (AHP) based on primary data from the survey filled out by the Ministry of Finance and local government officers to serve as the basis for budget reallocation in the future. The results of the analysis showed that printing, official uniforms, and food and beverages expenditures have the lowest priority score so they are proposed to be the main options for reallocation, while salaries and allowances expenditures have the highest priority score making it unfavorable for reallocation. These results can be used as the basis for the RG to determine the proper budget reallocation strategy so that it can be used as a reference in optimizing an efficient spending structure. This is expected to improve the impact of spending to enhance the quality of public services.